ESTABLISHING DRUG EFFECTS ON ELECTROCORTICOGRAPHIC ACTIVITY IN A GENETIC ABSENCE EPILEPSY MODEL: ADVANCES AND PITFALLS MODERN PRINCIPLES AND TECHNICAL SUPPORT OF RESEARCH ON THE MODEL OF GENETIC FORM OF ABSENT EPILEPSY - Luijtelaar, G. van; Oijen, G. van (Medical Informatics and Engineering, 2020)
Background. The identification of a valid experimental model of absence epilepsy is important for the investigations of its mechanisms and for the evaluation and justification of new experimental treatment options. The genetic rat models such as rats of the WAG/Rij strain and GAERS were developed as models for generalized genetic epilepsy and, in particular, for childhood absence epilepsy, and are currently at the forefront of new theoretical insights regarding the site of origin of absence epilepsy. Material and methods. In this review article, 40-years of experience in the field of experimental absence epilepsy is summarized in order to work out suitable and most optimal protocols for the proper evaluation of treatment, often drug effects on the electroencephalogram of genetic WAG/Rij rat. Results. The genetic absence epilepsy animal models, first described in the eighties of the previous century, have, among others, face, construct, and predictive validity. Genetic models were and are currently used as models to predict the action of antiepileptic medication and other experimental treatments, to elucidate neurobiological mechanisms of the for absence epilepsy characteristic spike-wave discharges and to study epileptogenesis. The electroencephalogram or electrocorticogram is imperative for recognizing absence seizures and for quantifying the spike-wave discharges, monitoring the animal's behavior is equally necessary for proper interpretation of the electroencephalogram data. Here an overview is given regarding the design of drug evaluation studies, which animals to use, classical and new electroencephalogram variables, among other wavelet analyses and various types of network analyses, the necessity of monitoring and quantification of the rats' behavior during the electroencephalogram registration, some pitfalls regarding the interpretation of the data, and some recent developments in electroencephalogram technology. Conclusions. The genetic models have replaced the pharmacological seizure models considering that it is possible to study mechanisms in a truly epileptic brain, although it is acknowledged that also the seizure models have a great merit. The predictive validity is better than in the previously used pharmacologically induced seizure models. Combined electroencephalogram-behavioural studies in adult symptomatic male and female WAG/Rij rats have a great potential to predict both anti-and proabsence actions of treatments and compounds.